Primary health care in pandemics: barriers, challenges and opportunities - Khoja,TAM; Qidwai,W; Rawaf,S; Alnaser,FA; Nanji,K; Khoja,A; Kurashi,NYA; Saad,NES; Halasa,W; Farahat,TM; Al,Shafaee M; Al,Shetti M; et al. (World Family Medicine Journal incorporating the Middle East Journal of Family Medicine, 2021)
COVID-19 has become a major global public healththreat. It started from Wuhan a province of China inDecember 2019 and has spread in every countryof the globe with over 100 million people currentlyinfected and over three million deaths as of May2021. Nearly a year on, with many town and citiesare in lockdown and with all public health measuresto minimize transmission of the virus SARS-COV2 and the scientific achievements with many vaccines developed in record time, the transmission inthe second wave is still strong with new variantsof the virus emerging. The pandemic has causeda serious impact on the economic, social, political,and cultural dynamics of people, globally. The majority of people with mild and moderate symptomsof COVID-19 seek primary care (PC) service as theentry point for getting medical intervention, reducing flow to hospital care. Currently, primary caresettings are facing major challenges including lackof funds, poor infrastructure in some countries, andshortage of health care workers and equipment.Most, if not all primary care centers are not designed to separate people with the virus. The pandemic so far shows that strengthening primary careas the first point of contact with the health systemis vital. The health systems of the future cannot beresilient without strong primary care for all, capableof meeting population health needs and aspirationfor good health and well-being.